ChemInform Abstract: Dicobalt‐μ‐oxo Polyoxometalate Compound, [(α2‐P2W17O61Co) 2O]14‐: A Potent Species for Water Oxidation, C—H Bond Activation, and Oxygen Transfer. Issue 16 (22nd April 2014) - Barats‐Damatov, Delina; Shimon, Linda J. W.; Weiner, Lev; Schreiber, Roy E.; Jimenez‐Lozano, Pablo; Poblet, Josep M.; de Graaf, Coen; Neumann, Ronny
Abstract The highly reactive species [(α2‐P2W17O61Co) 2O]14‐ containing a nearly linear Co—O—Co moiety is prepared by oxidation of [α2‐P2W17O61Co II(H2O)]8‐ and characterized by single crystal XRD, 31 NMR, Raman, and UV/VIS spectroscopy, and DFT calculations.